Necessity entrepreneurship: problems and ways to overcome them - Kuzmenko, Tatyana V. (Journal of the Belarusian State University. Sociology, 2019)
The factors that influence the motivation of entrepreneurial activity are analyzed in the article. On the materials of empirical research, the features of necessity entrepreneurship and the associated social risks and ways to overcome them are considered. The contradictions between the relative ease of opening and registering a business and the lack of tools and skills for carrying out further economic activities for necessity entrepreneurs are revealed. The idea that the forced nature of entrepreneurial activity can’t serve as an incentive for innovative transformations, and the transformation of entrepreneurship into a factor of economic growth requires conditions that contribute not only to increasing the number of small enterprises, but also to their effective development is justified. As the most important directions for the development of entrepreneurship, it is proposed to stimulate voluntary entrepreneurship, to reorient support tools from financial to training, to create an effective system of business education.
Keywords: entrepreneurship; small business; necessity entrepreneurship; voluntary entrepreneurship; business activity; institutional environment; motivation of entrepreneurial activity; adaptation